МАЛОИНЕРЦИОННЫЙ ТЕПЛООБМЕННИК АММИАК-АНТИФРИЗ ДЛЯ ИССЛЕДОВАНИЯ ПЕРЕХОДНЫХ ПРОЦЕССОВ В ЭЛЕМЕНТАХ ДВУХФАЗНОЙ СИСТЕМЫ ТЕРМОРЕГУЛИРОВАНИЯ СПУТНИКА - Годунов, Артем Михайлович; Роговой, Евгений Эдуардович; Орлов, Роман Сергеевич; Турна, Рустем Юсуфович (Avìacìjno-kosmìčna tehnìka ì tehnologìâ, 2019)
Technical progress entails the use of more powerful equipment on satellites. In connection with the growth of heat generation onboard the spacecraft, the task is to develop thermal control systems based on two-phase mechanically pumped fluid loop (2PMPFL). The advantage of such systems is the ability to transport a greater amount of heat, reduced to a unit of flow, than when using circuits with a single-phase coolant. The study of two-phase thermal control systems in terrestrial conditions is difficult because gravity affects the hydraulics and heat transfer of two-phase flows. Particularly difficult is the study of transients. This article presents the results of tests of a recuperative heat exchanger, which allows to study transient processes in 2PMPFL with high accuracy.It was designed and manufactured the heat exchanger of simple “tube in tube” type design. The thermal characteristics of the heat exchanger were determined on the experimental stand, which is a prototype of a closed-type 2PMPFL with ammonia coolant. Single-phase “liquid” modes, two-phase modes with low mass vapor content (up to 0.04), and single-phase transient modes were investigated. It has been experimentally determined that a heat exchanger under given conditions is capable of removing up to 1323 W of heat in a single-phase mode and up to 1641 W of heat - when operating in a two-phase mode. The data obtained in the course of the experiments allowed us to select the most appropriate known correlation for calculating the stationary characteristics of the heat exchanger with an error not exceeding 5%, which is a high indicator of accuracy for engineering calculations.The heat exchanger has low thermal inertia. The conclusion is relevant for the range of parameters: the ammonia temperature at the inlet is 24...60 ⁰C; antifreeze inlet temperature 5… 16 ⁰C; ammonia mass flow rate 8...17 g / s; mass flow rate of antifreeze 1...4 kg/min.Due to the low thermal inertia of the heat exchanger, it can be used to study transients with the rate of change of the coolant temperature at the inlet up to 1.85 K / min. You can use the stationary method of thermal calculation, i.e. calculate the transient process in the quasi-stationary approximation.